The role of occupational factors in the development and course of respiratory sarcoidosis - Inna A. Palchikovа; Olga A. Denisovа; Galina M. Chernyavskaya; Tatiana P. Kalacheva; Igor L. Purlik; Elena V. Bolotova (Терапевтический архив, 2021)
Aim. The aim of the study was to study the frequency of occurrence of exposure to harmful occupational factors in patients with sarcoidosis of the respiratory organs, depending on the course of the disease.